Coronary Artery Spasm and Perivascular Adipose Tissue Inflammation: Insights From Translational Imaging Research. Issue 1 (April 2019) - Ohyama, Kazuma; Matsumoto, Yasuharu; Shimokawa, Hiroaki
No abstract available